2021
DOI: 10.1101/2021.05.06.442994
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dendritic spine morphology regulates calcium-dependent synaptic weight change

Abstract: Dendritic spines act as computational units and must adapt their responses according to their activation history. Calcium influx acts as the first signaling step during postsynaptic activation and is a determinant of synaptic weight change. Dendritic spines also come in a variety of sizes and shapes. To probe the relationship between calcium dynamics and spine morphology, we used a stochastic reaction-diffusion model of calcium dynamics in idealized and realistic geometries. We show that despite the stochastic… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 120 publications
(316 reference statements)
0
5
0
Order By: Relevance
“…We hypothesized that multiple concentric layers would likely impede transport of ATP out of, and ADP into, the mitochondria of SFA3/SFA4 and Δ atp20 cells. To explore this hypothesis, we employed an MCell-based reaction-diffusion simulation pipeline for modeling ATP generation using EM-derived morphologies 9698 . These simulations showed that mitochondria with multiple IMM layers cause lower ATP generation when cytosolic ADP concentration was kept constant (Figure 2F, 2G, 2H).…”
Section: Resultsmentioning
confidence: 99%
“…We hypothesized that multiple concentric layers would likely impede transport of ATP out of, and ADP into, the mitochondria of SFA3/SFA4 and Δ atp20 cells. To explore this hypothesis, we employed an MCell-based reaction-diffusion simulation pipeline for modeling ATP generation using EM-derived morphologies 9698 . These simulations showed that mitochondria with multiple IMM layers cause lower ATP generation when cytosolic ADP concentration was kept constant (Figure 2F, 2G, 2H).…”
Section: Resultsmentioning
confidence: 99%
“…While in Figure 3, we show only minor changes in state and overall signaling effect, as stimulus frequency increases, cytosolic calcium concentration and ATP consumption also increase (Figure 4d-e). The change in calcium concentration is dependent on the frequency of glutamate stimulus (Figure 4d); as stimulus frequency increases, calcium amplitude increases and the higher frequencies are filtered out (also see [2, 60]). There is a corresponding ATP consumption that leads to an increase in the AMP/ATP ratio (Figure 4e), which leads to AMPK activation (Figure 4f).…”
Section: Resultsmentioning
confidence: 99%
“…Calcium signal transduction in dendritic spines during neuronal signaling is closely linked to synaptic plasticity [1][2][3][4][5]. Synaptic plasticity is the structural and molecular modification of synapses resulting in sustained changes in synaptic signaling strength [2,6,7]. There are many potential mechanisms by which calcium signaling leads to long-term plasticity (LTP), the process by which synaptic connections are strengthened with high-frequency stimulus, but the relative contribution of these different mechanisms is unclear [8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations